2012
DOI: 10.1590/s0074-02762012000500008
|View full text |Cite
|
Sign up to set email alerts
|

Asymptomatic infection with Plasmodium falciparum and Plasmodium vivax in the Brazilian Amazon Basin: to treat or not to treat?

Abstract: In this study, we determined whether the treatment of asymptomatic parasites carriers (APCs)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 25 publications
(37 reference statements)
1
14
0
Order By: Relevance
“…This scenario probably has a significant epidemiological impact on the transmission dynamics of malaria in endemic areas such as Africa [11] and the Brazilian Western Amazon [12] with a high number of asymptomatic carriers of gametocytes. Moreover, Katsuragawa et al .…”
Section: Discussionmentioning
confidence: 99%
“…This scenario probably has a significant epidemiological impact on the transmission dynamics of malaria in endemic areas such as Africa [11] and the Brazilian Western Amazon [12] with a high number of asymptomatic carriers of gametocytes. Moreover, Katsuragawa et al .…”
Section: Discussionmentioning
confidence: 99%
“…After treating all identified symptomatic and asymptomatic P. falciparum parasite carriers in the riverside locality of Vila Candelária, no more clinical cases of falciparum malaria were observed in the following year. However, the number of clinical P. vivax cases doubled in this locality, from 53 in the previous year to 105 in the following year (Tada 2008, Tada et al 2012). Both observations might be explained if clearing of the P. falciparum parasites results in the elimination of an "inhibitory signal", affecting the multiplication of P. vivax parasite cells, either of hypnozoite origin or from a quiescent infection.…”
Section: Discussionmentioning
confidence: 93%
“…These sera were collected between 2006-2008 in the Malaria Post of the Centre for Research in Tropical Medicine (CEPEM). (ii) Another group of sera was obtained from asymptomatic individuals patients living in the malaria endemic localities in the suburban and rural localities of Vila Candelária, Cachoeira do Teotônio, Santo Antônio and Vila Amazonas of Porto Velho (Tada et al 2012). Asymptomatic sera were thus classified as those from individuals in the same localities, with positive PCR for P. vivax and/or P. falciparum and without recorded clinical symptoms for at least 30 days period after the positive PCR diagnosis.…”
Section: Subjects Materials and Methodsmentioning
confidence: 99%
“…Several works showed that residual malaria may resist to conventional treatment [1215]. Thus, the APC presence, associated with ineffective tools for vector control and population mobility in Amazon, can be regarded as important factors to explain the increase and maintenance of malaria [16].…”
Section: Introductionmentioning
confidence: 99%
“…The ineffectiveness can be attributed to relapses that occur after the complete treatment (CQ plus PQ) of symptomatic patients and APC. Thus, in these areas the clinical immunity observed to P. vivax is not species specific but only strain specific [15]. …”
Section: Introductionmentioning
confidence: 99%